Participatory Culture Communication in the Preservation of Sundanese Manuscripts - Parama Artha, Luthfi; Ratnasari, Anne; Kurniadi, Oji (Kirana Publisher (KNPub), 2023)
As relics of the past, ancient manuscripts are able to provide information on various aspects of the lives of past communities such as politics, economics, socio-culture, traditional medicine, the veil of earthquakes or natural phenomena, human physiology, and so on. The values of this information are needed to relate the good values of the past to be applied today. Media offerings related to Sundanese manuscripts are limited. Among of limited information from the website, www.kiraga.com emerged as one of the public parties that participated to preservation of this cultural heritage, especially in the scope of Sundanese manuscripts. Participation culture is defined as a new form of culture that develops due to the support of information technology, where individuals or members of a community can participate in the creation and distribution of content. This research is qualitative research with case study method, researchers try to analyze the participatory culture of kairaga.com website in preserving Sundanese manuscripts. The data collection techniques used are interviews, observation, and documentation. From the results of the research, the website manager collaborated with Pustaka Sunda, Sakola Aksara Sunda Cianjur, Masyarakat Pernaskahan Nusantara (Manassa), Jagongan Naskah (Jangkah) with various circles of Sundanese manuscript lovers both from within and outside country to become an integral part of cultural expansion because it increases the community's ability to collaborate, namely developing and disseminating news, ideas, and creative works and connecting with people who have the same goals and interests in this case content development.